AGR680: Research Project II / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (2018)
Final year students are required to carry out a project under the supervision of one or two lecturers in the faculty. The project outcome must be presented orally to the faculty. The project report will be submitted to the supervisor(s). Both oral presentation and project report will be assessed. The commitment, discipline and creativity of the student in conducting the project, data collection, data analysis, discussion and concluding the project will also be assessed.